2019
DOI: 10.1007/s10803-019-04115-9
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of the TOBY Application, an iPad Intervention for Children with Autism Spectrum Disorder: A Thematic Approach

Abstract: This study aimed to explore the appropriateness of an ICT intervention, the Therapeutic Outcomes by You application (TOBY app), from the perspectives of the parents. Parental experiences of twenty-four parents of a child with ASD who had participated in a three-month trial using the TOBY app were collected using semi-structured interviews. Thematic analysis was conducted and themes were mapped against an appropriateness framework. Collectively, parents felt the TOBY app was relevant and important to them and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…One of the premises supported by almost all the literature is the need for customisation of technology [18,22,32,33,35,37,[39][40][41][42][44][45][46][47][48][49]. In this study, the elements identified as customisable for each child were images, sound, reinforcement, text, colours, screen layout and presentation, and content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the premises supported by almost all the literature is the need for customisation of technology [18,22,32,33,35,37,[39][40][41][42][44][45][46][47][48][49]. In this study, the elements identified as customisable for each child were images, sound, reinforcement, text, colours, screen layout and presentation, and content.…”
Section: Discussionmentioning
confidence: 99%
“…The need to involve children with ASD, family members and professional interdisciplinary team members in the design of technology emerged from interviews and observations, as previously described in several publications [22,33,38,42,[46][47][48][49]. Several authors have implemented studies to capture the perspectives on technology design of end-users and stakeholders in participatory design from a qualitative or mixed approach [22,41,42,[44][45][46]49]. It is also necessary to properly select knowledge extraction techniques to help children, relatives and professionals capture their perspectives [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…however, further research into the parent and child factors that influence the maintenance of skills is warranted (Parsons, Wilson, Vaz, Lee, & Cordier, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even simple features such as task lists, calendars and address book applications can improve the day-to-day independence of school-going young people with ASD (Gentry et al, 2010 ; Hedges et al, 2018 ). Smartphone applications can potentially provide parents and carers with objective early screening (Egger et al, 2018 ; Kanne, et al, 2018 ) and intervention tools (Law et al, 2018 ; Parsons et al, 2019 ; Rogerson et al, 2019 ). Using online social media platforms (e.g.…”
Section: Introductionmentioning
confidence: 99%